Mitofusins: Disease Gatekeepers and Hubs in Mitochondrial Quality Control by E3 Ligases - Escobar-Henriques, Mafalda; Joaquim, Mariana (Frontiers in Physiology, 2019)
Mitochondria are extremely dynamic organelles engaged in quality control and aging processes. These double membrane organelles constantly undergo fusion, fission, transport and anchoring events, which empower mitochondria with a very interactive behaviour. The membrane remodelling processes needed for fusion between two outer membranes require extremely conserved proteins named mitofusins. Mitofusins, MFN1 and MFN2 in mammals and Fzo1 in yeast, are the first determinants deciding on whether communication and content exchange between different mitochondrial populations should occur. Importantly, each cell possesses hundreds of mitochondria with a different severity of mitochondrial mutations or dysfunctional proteins, which potentially spread damage to the entire network. Therefore, the degree of their merging capacity critically influences cellular fitness. In turn, the mitochondrial network rapidly and dramatically changes in response to metabolic and environmental cues. Notably, stress experienced by neurons and cardiomyocytes, but also cancer or obesity conditions, trigger the downregulation of mitofusins and thus fragmentation of mitochondria. This places mitofusins upfront in sensing and transmitting stress. In fact, mitofusins are almost entirely exposed to the cytoplasm, a topology suitable for a critical relay point in information exchange between mitochondria and their cellular environment. Mitofusins are either activated or repressed by post-translational modifiers, mainly by ubiquitin. Ubiquitin is a ubiquitous small protein orchestrating multiple quality control pathways, which is covalently attached to lysine residues in its substrates, or in ubiquitin itself. Importantly, E3 ligases perform the ultimate and determinant step –from a chain of events also mediated by E1 and E2 enzymes– in substrate choice for covalent binding of ubiquitin. Here, we review the ubiquitin E3 ligases that modify mitofusins. Two mitochondrial E3 enzymes –March5 and Mul1– one located to the ER –Gp78– and three cytosolic –MGRN1, HUWE1 and Parkin– were shown to ubiquitylate mitofusins, in response to a variety of cellular inputs. The respective outcomes on mitochondrial morphology and contact sites to the endoplasmic reticulum and on destructive processes like mitophagy or apoptosis are presented. Ultimately, understanding the mechanisms by which E3 ligases and mitofusins sense and bi-directionally signal mitochondrial-cytosolic dysfunctions could pave the way for therapeutic approaches in neurodegenerative, in cardiovascular and in obesity-linked diseases.